2019
DOI: 10.1158/0008-5472.can-18-1995
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Overexpression Reveal Distinct Oncogenic Roles for Different Type I Protein Arginine Methyltransferases

Abstract: Protein arginine methyltransferases (PRMTs) are generally not mutated in diseased states, but they are overexpressed in a number of cancers, including breast cancer. To address the possible roles of PRMT overexpression in mammary gland tumorigenesis, we generated Cre-activated PRMT1, CARM1 and PRMT6 overexpression mouse models. These three enzymes are the primary Type I PRMTs and are responsible for the majority of the asymmetric arginine methylation deposited in the cells. Using either a keratin 5-Cre recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…1C and D). Consistent with our observations, a recent report demonstrated hyperbranching of the mammary glands and increased ki-67 staining in the breast epithelium of PRMT6 GOF transgenic mice (25).…”
Section: Overexpression Of Prmt6 Drives De Novo Hyperproliferation Insupporting
confidence: 93%
“…1C and D). Consistent with our observations, a recent report demonstrated hyperbranching of the mammary glands and increased ki-67 staining in the breast epithelium of PRMT6 GOF transgenic mice (25).…”
Section: Overexpression Of Prmt6 Drives De Novo Hyperproliferation Insupporting
confidence: 93%
“…Notably, recent studies indicate that the role of CARM1 is complex and context‐dependent in cancer development, which functions both as a tumor‐suppressor and as a tumor‐promoting protein . Importantly, in vivo studies have shown the oncogenic activities of CARM1 in breast cancer ; nevertheless, the molecular basis of this complexity in CARM1's action remained largely unexplored prior to this study. Our study demonstrates that CARM1 and LSD1 are highly expressed in human breast cancerous tissues compared with the non‐cancerous tissues (Fig EV2), and CARM1 expression is elevated in malignant breast cancer (Fig D) and is positively correlated with LSD1 R838me2a and LSD1 levels (Fig F and G), suggesting a tumor‐promoting role of this protein in breast carcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, PRMTs are de-regulated in several types of cancer [39] and in particular PRMT1 overexpression was shown to positively correlate with tumor progression [84,85]. Also, a recent study has showed that the overexpression of type-I PRMTs, including PRMT1, promotes mammary gland tumorigenesis in mice [86]. Similarly, microRNA expression is often altered in cancer, where these molecules can display either oncogenic or tumour-suppressive functions [87][88][89].…”
Section: Discussionmentioning
confidence: 99%